2020
DOI: 10.3390/ijms21062138
|View full text |Cite
|
Sign up to set email alerts
|

Hericium Erinaceus Prevents DEHP-Induced Mitochondrial Dysfunction and Apoptosis in PC12 Cells

Abstract: Hericium Erinaceus (HE) is a medicinal plant known to possess anticarcinogenic, antibiotic, and antioxidant activities. It has been shown to have a protective effect against ischemia-injury-induced neuronal cell death in rats. As an extending study, here we examined in pheochromocytoma 12 (PC12) cells, whether HE could exert a protective effect against oxidative stress and apoptosis induced by di(2-ethylhexyl)phthalate (DEHP), a plasticizer known to cause neurotoxicity. We demonstrated that pretreatment with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Several studies have shown that H. erinaceus mycelium can stimulate the synthesis of NGF for neuroprotection and prevents neurodegenerative diseases [ 32 ]. Depression is a common neuropsychiatric conditions and abnormal behaviors can be improved by the H. erinaceus mycelium in animals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that H. erinaceus mycelium can stimulate the synthesis of NGF for neuroprotection and prevents neurodegenerative diseases [ 32 ]. Depression is a common neuropsychiatric conditions and abnormal behaviors can be improved by the H. erinaceus mycelium in animals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HESAE was shown to attenuate apoptosis following exposure to high-dose corticosterone. Likewise, a biomass preparation of H. erinaceus also showed protective activity against Di-2-ethylhexyl-phthalate (DEHP)-induced apoptosis mediated by caspase activation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…curcumin, resveratrol, flavonols present in Ginkgo biloba extracts, polyphenols present abundantly in the leaves and in the ripening fruits of the olive tree, Olea europaea ), as well as mushrooms ( Hericium Erinaceus , Coriolus versicolor ) can significantly modulate Nrf2 and Nrf2-dependent vitagenes expression, showing neuroprotective action. This can potentially resolve pathologies such as AD, PD and also Meniere’s Disease, another degenerative pathology ( Amara et al, 2020 , Trovato et al, 2016a , Trovato et al, 2016b , Trovato Salinaro et al, 2018 , Scuto et al, 2019 ).…”
Section: Molecular Mechanisms Involving Ozone (O 3 mentioning
confidence: 99%